Hi there!
The question is asking us to simplify the expression (x² + 3x - 7)(2x - 5) and write the answer in standard form. Here is how you do that -
Original: (x² + 3x - 7)(2x - 5)
Break it apart - [(x² + 3x - 7)(2x)] + [(x² + 3x - 7)(-5)]
Simplify -
2x³ + 6x² - 14x - 5x² - 15x + 35
Now, combine like terms -
2x³ + x² - 29x + 35
Therefore, the answer to your query is 2x³ + x² - 29x + 35. Hope this helps!
Answer:
2
Step-by-step explanation:
calculator
Answer:
The slope is 45.
Step-by-step explanation:
Using the slope formula by two points:
m=(y2-y1)/(x2-x1)
m=(210-120)/(4-2)
m=45
Answer:
36, 180
Step-by-step explanation:
x = y/5, so y = 5x
y - x = 144
5x - x = 144
4x = 144
x = 144/4 = 36
y = 5x = 5*36 = 180
The two numbers are 36 and 180